Enabling AC electroluminescence in quasi-2D perovskites by uniformly arranging different-n-value nanoplates to allow bidirectional charge transport. (January 2021) - Zhang, Jia; Tsai, Hsinhan; Nie, Wanyi; Hu, Bin
Abstract: Perovskite light-emitting diodes (LEDs) are normally operated under forward direct current (DC) to realize electron/hole injection at cathode/anode surfaces. Here, we demonstrate an alternating current (AC) driven LED enabled by bi-directionally allowed charge transport in quasi-2D perovskite (PEA2 MAn−1 Pbn I3n+1 ) film. Essentially, the bi-directional charge transport is realized by uniformly arranging different-n-value 2D nanoplates together with symmetrically designed anode/cathode interfaces, which can allow injected electrons and holes to form light-emitting states under both forward and reverse biases, leading to an AC electroluminescence (EL) with the device architecture of ITO/PEI/PEDOT:PSS/PEA2 MAn−1 Pbn I3n+1 /P3HT/PEI/Ag. The high AC EL performance was achieved with the radiance = 24 W Sr −1 m −2 and 18.3 W Sr −1 m −2 and EQE = 12.5% and 3.7% under forward and reverse biases. The device-operational stability was largely improved with the half-intensity time of T50 = 11.0 h under AC bias (+2 V/−2 V, 50 Hz) as compared to T50 = 3.9 h under forward bias (+2 V/0 V, 50 Hz). Graphical Abstract: ga1 Highlights: Demonstrating efficient quasi-2D perovskite AC LED for the first time. Uniformly arranging 2D nanoplates to allow bidirectional charge transport. Symmetrically designing device structure to enable forward and reverse injection. Largely improving operational stability under AC-driven condition.